Forecasting Policy Pemindahan Kegiatan Pemerintahan Terhadap Pembangunan di Wilayah Selatan Kota Mataram - Aprian Jailani, Muhammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
Forecasting Policy is an approach to predicting phenomena that will occur in the future through data. The purpose of the research is as a basis for policy makers to minimize the occurrence of the same empirical problems encountered in the current government location in the Mataram City government in the Southern Region. This research uses a descriptive and qualitative approach with a triangulation analysis model. The results showed that the transfer of administration to the southern region in the policy forecasting approach had problems that in the lamp also occurred in various aspects such as the economy (street vendors, stalls et cetera), the environment, traffic, and particularly like prisons which are activities every year in the Mataram City area or more directed to cultural aspects. However, this impact does not rule out the possibility of obtaining improvement and development of places in the southern region of Mataram City.